If a=5–√+15–√−1b = 5–√−15–√+1then the value of(a2+ab+b2a2−ab+b2) is = ?If a=5+15−1b = 5−15+1then the value of(a2+ab+b2a2−ab+b2) is = ?\eqalign{ & {\text{If }}a = \frac{{\sqrt 5 + 1}}{{\sqrt 5 - 1}} \cr & b{\text{ = }}\frac{{\sqrt 5 - 1}}{{\sqrt 5 + 1}} \cr & {\text{then the value of}} \cr & \left( {\frac{{{a^2} + ab + {b^2}}}{{{a^2} - ab + {b^2}}}} \right){\text{ is = ?}} \cr} " /> If a=5–√+15–√−1b = 5–√−15–√+1then the value of(a2+ab+b2a2−ab+b2) is = ?If a=5+15−1b = 5−15+1then the value of(a2+ab+b2a2−ab+b2) is = ?\eqalign{ & {\text{If }}a = \frac{{\sqrt 5 + 1}}{{\sqrt 5 - 1}} \cr & b{\text{ = }}\frac{{\sqrt 5 - 1}}{{\sqrt 5 + 1}} \cr & {\text{then the value of}} \cr & \left( {\frac{{{a^2} + ab + {b^2}}}{{{a^2} - ab + {b^2}}}} \right){\text{ is = ?}} \cr} " /> If a=5–√+15–√−1b = 5–√−15–√+1then the value of(a2+ab+b2a2−ab+b2) is = ?If a=5+15−1b = 5−15+1then the value of(a2+ab+b2a2−ab+b2) is = ?\eqalign{ & {\text{If }}a = \frac{{\sqrt 5 + 1}}{{\sqrt 5 - 1}} \cr & b{\text{ = }}\frac{{\sqrt 5 - 1}}{{\sqrt 5 + 1}} \cr & {\text{then the value of}} \cr & \left( {\frac{{{a^2} + ab + {b^2}}}{{{a^2} - ab + {b^2}}}} \right){\text{ is = ?}} \cr} " />
Post your Comments